Birs: A System of General Purpose Computer Programs for Information Retrieval in the Behavioral Sciences - Vinsonhaler, John F. (The American behavioral scientist (Beverly Hills), 1967)
In contrast to most information retrieval programs, which are usually written in machine language or for some special- purpose compiler, BIRS is written entirely in FORTRAN IV and should be readily adapted to many university computing installations. John Vinsonhaler is Acting Director of the Computer Institute for Social Science Research, Michigan State University.